IMPLEMENTASI SERTIFIKASI HALAL PADA PRODUK UMKM DI DESA PANONGAN DALAM PRESPEKTIF HUKUM EKONOMI SYARIAH - Annur Safitri Gusduriyah; Akhmad Aflaha, Moh. Wahyudin, Syukron (Jurnal Ekonomi dan Bisnis, 2025)
The main point in this research is regarding the Implementation of Certification for Halal Products in Panongan Village (Law Number 33 of 2014 concerning Halal Product Guarantees) regarding the obligation to certify halal food and beverage products for MSMEs in Panongan Village. This research uses a qualitative research method with an empirical juridical approach. Empirical approach research is legal research that is used to see how law is practiced, thus law is not only about the enactment or implementation of normative legal provisions on each particular event, but is also a social process and social institution. In this research, the author determined that the subjects in this research were MSME actors and PPH assistants in Panongan Village, while determining the object of this research was to determine the obligation to implement halal certification for MSMEs in Panongan Village. The results of this research show that the implementation of halal certification for MSME products in Panongan Village (Law Number 33 of 2014 concerning Halal Product Guarantees) has been implemented although it is not yet effective because there are still MSME actors in the food sector who do not yet have a halal certificate. The existence of mandatory halal certification for food and beverage products has not made business actors aware of being able to process halal certification for the business products they make. Even though the majority of the people of Panongan Village are Muslim, there are still food and beverage products that do not have halal certification which is caused by a lack of knowledge and understanding of MSME actors regarding halal certification, low awareness and compliance of MSME actors to register halal certification on their products, MSME actors' confidence in halalness. its products, as well as the prevalence of ancient societal ideas that oppose the existence of regulations of an institution.